When Do Salps Bloom? Engaging Primary Students in Underwater Citizen Science - Aguayo, C; Decima, M (The Centre for Learning and Teaching (CfLAT), AUT University, 2020)
When do Salps bloom? In this MBIE Curious Minds funded project we sought to address the growing need to involve people at a young age in learning involving active scientific research, to enhance societal understanding of science and technology and promote careers in STEM/STEAM to groups traditionally less represented. We engaged Leigh Primary School children with Salp research led by Dr Moira Decima from NIWA, and with citizen science through involvement in the co-design of a mobile app to report salp (marine invertebrate) sightings in coastal and underwater environments in our case study site: Goat Island Marine Reserve. The goal of the project was to engage students in cutting-edge marine science research and conservation; and in technological development through the co-design of a mobile app to report salps sightings in local coastal environments.
Keywords: Citizen science; Digital co-design; Primary students; STEAM; Salp research